2019
DOI: 10.1002/star.201900147
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transport in Starch Exposed to Ionizing Radiation: Experiment Versus Theoretical Computer Modeling

Abstract: The paper deals with the experimental and theoretical study of the temperature distribution in granular starch exposed to ionizing radiation. In this respect, corn starch is irradiated by using a field of accelerated electrons of mean energy of 5.5 MeV for a period of 435 s. A sensor is placed inside the starch sample to record the temperature during irradiation and after irradiation until room temperature is reached again. From a theoretical point of view, in order to describe the temperature field, a mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…It was observed that there are three major stages: (i) heating during irradiation, up to t = 435 s, (ii) post-irradiation heating, up to the maximum temperature is reached, and (iii) cooling to the room temperature. This finding is consistent with the fact that the heat continues to propagate in starch for a while, in connection with the place where the sensors are placed, after the irradiation process is stopped and before the cooling process begins [13]. The maximum temperature and the moment of its reaching differ for the two types of investigated starch, both in the first sensor, S1potato and S1corn, but even more visible in the second sensor, S2potato and S2corn.…”
Section: Temperature Profilesupporting
confidence: 85%
See 1 more Smart Citation
“…It was observed that there are three major stages: (i) heating during irradiation, up to t = 435 s, (ii) post-irradiation heating, up to the maximum temperature is reached, and (iii) cooling to the room temperature. This finding is consistent with the fact that the heat continues to propagate in starch for a while, in connection with the place where the sensors are placed, after the irradiation process is stopped and before the cooling process begins [13]. The maximum temperature and the moment of its reaching differ for the two types of investigated starch, both in the first sensor, S1potato and S1corn, but even more visible in the second sensor, S2potato and S2corn.…”
Section: Temperature Profilesupporting
confidence: 85%
“…All these aspects actually underline the importance of knowing the dynamics of the temperature in starch during irradiation in order to control the final results of irradiation. In our previous work [ 13 ] on this topic, we reported a first theoretical approach concerning the temperature distribution in the granular corn starch exposed to electron beam irradiation through a semi-analytical model based on the heat equation in Cattaneo-Vernote formalism and solved by using the integral transform technique on finite domains. To the best of our knowledge, there are no other studies that explore this thematic area.…”
Section: Introductionmentioning
confidence: 99%
“…The electron accelerator installation is of traveling-wave type, using microwaves in the S-band at 2.99 GHz that propagate in a disk-loaded tube of about 2 m long; the microwaves are produced by an EEV-M5125 type magnetron that provides 2 MW of power in pulses of 4 μs [ 38 ]. The ALID-7 accelerator is used in different experimental researches in the field of radiation [ 21 , 39 , 40 , 41 ]. The sample irradiations were carried out with different irradiation doses ( = 0.7–1.2 kGy) and dose rates ( = 0.5–0.7 kGy/min) as shown in Table 2 , at the room temperature (25 ± 1 °C) and ambient pressure under air.…”
Section: Methodsmentioning
confidence: 99%
“…Brasoveanu et al [ 55 , 56 ] devised a mathematical model to represent the thermal distribution based on the Cattaneo–Vernote formalism’s heat equation, solved by ITT in finite domains. The model was used to calculate the relaxation time, the hottest point, and the peak thermal distribution intensity.…”
Section: Various Applications Of Integral Transform Technique (Itt): Fourier and Non-fouriermentioning
confidence: 99%
“… Temperature distribution in the irradiated potato and corn starches [ 55 , 56 ]; published under MDPI’s open access license. …”
Section: Figurementioning
confidence: 99%